2013
DOI: 10.1515/epoly-2013-0101
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the electrochemical properties of SBS-based anionic membranes by the amine molecular structure

Abstract: In this work, different amines (bifunctional, as diazabicyclo[2.2.2]octane (Dabco) and monofunctional, as N-methylimidazole or trimethylamine) were utilized for the amination of benzyl chloride-grafted polystyrene-b- poly(butadiene)-b-polystyrene triblock copolymers (SBS-g- VBC). The use of Dabco solutions in mixture with variable amounts of monoamine or at different concentration allowed to modulate the degree of crosslinking of the SBS-based membranes and their electrochemical parameters. More specifically, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
(34 reference statements)
2
12
0
Order By: Relevance
“…Nevertheless, if a certain crosslink among PVBC macromolecules occurs, it would be beneficial for the structural stabilization of the MEA. It has also been demonstrated that moderate amounts of crosslinking promoted by DABCO are able to decrease the water uptake, while not reducing ionic conductivity [30,32]. Fundamental properties; water uptake, ion-exchange capacity and ionic conductivity were not measured due to the poor mechanical properties after film casting.…”
Section: Ionomer Synthesis and Performancementioning
confidence: 99%
“…Nevertheless, if a certain crosslink among PVBC macromolecules occurs, it would be beneficial for the structural stabilization of the MEA. It has also been demonstrated that moderate amounts of crosslinking promoted by DABCO are able to decrease the water uptake, while not reducing ionic conductivity [30,32]. Fundamental properties; water uptake, ion-exchange capacity and ionic conductivity were not measured due to the poor mechanical properties after film casting.…”
Section: Ionomer Synthesis and Performancementioning
confidence: 99%
“…The presence of DABCO in the degradation product was conrmed by the bending deformation at 1460 cm À1 ( ) of the CH 2 groups 103 while the strong signal at 1030 cm À1 ( ) is due to C-N stretching vibrations in the DABCO structure. 104,105 4…”
Section: Ftir Analysis Of the Solid Degradation Productsmentioning
confidence: 99%
“…It is impossible to distinguish the various effects and the differential thermogravimetric curves (DTG) are more useful in this respect (see below). The residual mass of around 16 % at the end of the experiment belongs to oxides due to decomposition of the LDH; the difference with the initial percentage of LDH (30 %) is due to the loss of anions, as previously described [48,50].…”
Section: Degradation Test: Water Uptakementioning
confidence: 54%
“…In PPO-DABCO+LDH composites (Figure 8c), the first peak with a maximum near 150 °C belongs to removal of interlayer water of LDH [48,50]. In the broad signal starting around 200 °C, one can first observed the loss of DABCO with an intermediate maximum at 230 °C.…”
Section: Degradation Test: Water Uptakementioning
confidence: 94%